Primary High-Grade Angiosarcoma of the Breast in a Young Woman With Breast Implants: A Rare Case and a Review of Literature. (December 2020) - Russo, Daniela; Campanino, Maria Raffaela; Cepurnaite, Rima; Gencarelli, Annarita; De Rosa, Filippo; Corvino, Antonio; Menkulazi, Marsela; Tammaro, Vincenzo; Fuggi, Mariano; Insabato, Luigi
Primary angiosarcoma (AS) of the breast is an extremely unusual variant of breast malignancies, and its incidence is about 0.05% of all primary breast tumors. In this article, we present a rare case of a primary AS that developed in a young woman with breast implants. This case report emphasizes importance of early investigation for accurate diagnosis and proper management of the breast AS, along with a correlation of histopathologic, radiologic, and clinical findings.